1998
DOI: 10.1016/s1097-2765(00)80088-x
|View full text |Cite
|
Sign up to set email alerts
|

An Activator Target in the RNA Polymerase II Holoenzyme

Abstract: Expression of protein-coding genes in eukaryotes involves the recruitment, by transcriptional activator proteins, of a transcription initiation apparatus consisting of greater than 50 polypeptides. Recent genetic and biochemical evidence in yeast suggests that a subset of these proteins, called SRB proteins, are likely targets for transcriptional activators. We demonstrate here, through affinity chromatography, photo-cross-linking, and surface plasmon resonance experiments, that the GAL4 activator interacts di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
160
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(174 citation statements)
references
References 73 publications
9
160
0
5
Order By: Relevance
“…To determine whether Mediator has a role in recruitment of SAGA or Gal4, we performed ChIP assays in a strain harboring a temperature-sensitive mutation in the Mediator subunit Srb4, which is required for complex integrity (Koh et al 1998;Kang et al 2001). Figure 6C shows, as expected, that inactivation of Srb4 substantially decreased recruitment of Mediator (Srb2) to the UAS.…”
Section: The Gal4-tra1 Interaction Initiates An Ordered Protein Intermentioning
confidence: 57%
See 2 more Smart Citations
“…To determine whether Mediator has a role in recruitment of SAGA or Gal4, we performed ChIP assays in a strain harboring a temperature-sensitive mutation in the Mediator subunit Srb4, which is required for complex integrity (Koh et al 1998;Kang et al 2001). Figure 6C shows, as expected, that inactivation of Srb4 substantially decreased recruitment of Mediator (Srb2) to the UAS.…”
Section: The Gal4-tra1 Interaction Initiates An Ordered Protein Intermentioning
confidence: 57%
“…For example, in some assays direct interactions between Gal4 and Mediator have been detected (Koh et al 1998;Park et al 2000;Jeong et al 2001). Consistent with this possibility, Bryant and Ptashne (2003) reported that Mediator was recruited to the GAL1 promoter in an spt20⌬ mutant, prompting the suggestion that in the initial stages of activation, SAGA and Mediator are independently contacted and recruited by Gal4.…”
Section: An Ordered Protein-protein Interaction Pathway For Transcripmentioning
confidence: 86%
See 1 more Smart Citation
“…To address the role of Mediator in regulating PDR5 transcription, we analyzed the effect of inactivating Srb4 on PDR5 transcription. The Mediator subunit Srb4 is required for the integrity of the complex (45,46). Thermal inactivation of temperature-sensitive Srb4-2 caused a dramatic reduction of PDR5 transcription and, in fact, the effect of the srb4-2 mutation on PDR5 was noticeable even at 25°C (Fig.…”
Section: Pdr5mentioning
confidence: 99%
“…A fourth, less tightly associated module composed of Srb8, -9, -10, and -11 has also been isolated as a separate complex with kinase activity Borggrefe et al 2002). The head module includes eight tightly associated proteins (Koh et al 1998) and is thought to interact with the C-terminal domain (CTD) of RNA polymerase II (Lee and Kim 1998) and with two of the general transcription factors (TBP, TFIIB). The middle module with its eight subunits interacts with the CTD and TFIIE and the Srb8-11 module of the mediator (Kang et al 2001).…”
mentioning
confidence: 99%